Parental hesitancy towards vaccinating their children with a booster dose against COVID-19: Real-world evidence from Taizhou, China - Li-Li Huang; Yu-Pei Yang; Hui-ping Mao; Wei-wei Hu; Yan-hong Jiang; Zhu Liduzi Jiesisibieke; Tao-Hsin Tung (Elsevier, 2022)
Introduction: Parental vaccine-hesitancy can lead to delays or refusal to vaccinate children despite the availability of vaccines. This is a population-based, cross-sectional study investigating whether parents in China are hesitant to vaccinate their children with a COVID-19 vaccine booster. Methods: Parents in Taizhou, China, responded to a self-reported online questionnaire on their hesitancy to vaccinate their children with a COVID-19 vaccine booster. Of the 1252 parents who were invited to answer the structured questionnaire, 514 (41.1%) samples had valid data for data analysis. Results: A total of 41.8% of participants were hesitant to give their children a COVID-19 vaccine booster. After adjusting for confounders, parental gender (female vs. male parent, OR=0.56 95% CI: 0.32-0.87), parental opinion (yes vs. no, OR=0.17, 95% CI: 0.09-0.30), parental attitudes (yes vs. no, OR=0.28, 95% CI: 0.16-0.50), the presence of people around them who are generally hesitant to receive COVID-19 booster vaccines for children (yes vs. no, OR=0.14, 95%CI: 0.08-0.23), the individual hesitancy of people around them to administer booster COVID-19 vaccines to children (yes vs. no, OR=0.02, 95%CI: 0.02-0.22), and parents' hesitancy to receive a booster vaccine for their children showed significant correlation. The disparity of factors related to booster vaccine-hesitancy for children between fathers and mothers was also found. Conclusions: We found that a moderate proportion of parents reported that they were hesitant to give their children a COVID-19 vaccine booster. The results suggest that an in-depth, dynamic assessment and further health education planning are necessary to reduce Chinese parents' hesitancy to vaccinate their children.